ON THE HEURISTIC RULE FOR PLANETARY DISTANCE DISTRIBUTION - Svyazhyn, N. D. (Одеські астрономічні публікації, 2016)
This paper presents a new heuristic rule for the planetary distance distribution in the solar system similar to the Titius-Bode rule of planetary orbit spacing. Application of this universal rule simultaneously for planets and planetary moons has been considered. Natural satellites orbiting around a central body are divided into groups of six satellites in each